1998
DOI: 10.1128/jb.180.14.3704-3710.1998
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the GntII (Subsidiary) System for Gluconate Metabolism Reveals a Novel Pathway for l -Idonic Acid Catabolism in Escherichia coli

Abstract: The presence of two systems in Escherichia coli for gluconate transport and phosphorylation is puzzling. The main system, GntI, is well characterized, while the subsidiary system, GntII, is poorly understood. Genomic sequence analysis of the region known to contain genes of the GntII system led to a hypothesis which was tested biochemically and confirmed: the GntII system encodes a pathway for catabolism of l-idonic acid in whichd-gluconate is an intermediate. The genes have been named accordingly: the idnK ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…For all but six of the 218 assigned classical SDRs, the coenzyme specificity is correctly predicted, as judged by agreements with the annotations in the SWISSPROT database entries. Scrutinizing the six deviating cases, we find that in four (Dhb1_Human, Dhb7_Mouse, Dhpr_Rat and Idno_Ecoli) there are experimental studies [14][15][16][17] that support our predictions. The remaining two cases are sequences involved in fatty acid biosynthesis (Fabg_Thema and Fag2_Syny3).…”
Section: Subfamilies Within the Classical Sdr Familysupporting
confidence: 62%
See 1 more Smart Citation
“…For all but six of the 218 assigned classical SDRs, the coenzyme specificity is correctly predicted, as judged by agreements with the annotations in the SWISSPROT database entries. Scrutinizing the six deviating cases, we find that in four (Dhb1_Human, Dhb7_Mouse, Dhpr_Rat and Idno_Ecoli) there are experimental studies [14][15][16][17] that support our predictions. The remaining two cases are sequences involved in fatty acid biosynthesis (Fabg_Thema and Fag2_Syny3).…”
Section: Subfamilies Within the Classical Sdr Familysupporting
confidence: 62%
“…However, the ratio between extended and classical forms is still the same when reducing the data set for homology at the 60% and 80% levels. The absolute numbers of extended SDRs are similar in the animal species (10)(11)(12)(13)(14)(15)(16)(17)(18). The number of classical SDRs is between 39 and 48 in human, mouse and fruit fly, while the worm has 72 classical SDRs.…”
Section: Application To Genome Datamentioning
confidence: 93%
“…Brisse et al showed that the utilization of 5-keto-D-gluconate was positive for all the test (six of six) K. variicola strains and was negative for all the test (nine of nine) K. quasipneumoniae strains [6]. We found that the idnO gene encoding 5-keto-D-gluconate 5-reductase, which catalyzes a reversible reduction of 5-ketogluconate to form D-gluconate [24], was present in the genomes of all the 22 strains belonging to K. variicola and was absent in the genomes of all the eight strains belonging to [6]. We found that the sorCDFBAME operon required for the catabolism of L-sorbose [25] was present in the genomes of all the 22 strains belonging to K. variicola and was absent in the genomes of all the five strains belonging to K. quasipneumoniae subsp.…”
Section: Resultsmentioning
confidence: 58%
“…For instance, providing glycerol as the sole carbon source instead of glucose increases expression of glpX, part of the glp operon, which is involved in glycerol uptake 23 . Gluconate as a carbon source increases expression of genes from the gnt and idn operons, both involved in gluconate metabolism 24,25 . Finally, using lactate as a carbon source induces the expression of lldD (lctD), a gene required for lactate utilization in E. coli 26 .…”
Section: Discussionmentioning
confidence: 99%